Does Healthy Living Matter to Work Outcomes? Effects of Exercise and Health Conscious Identity on Employee Job Performance and Life Satisfaction (Journal of Organizational Psychology, 2023)
Organizational behavior and human resource management scholarship and practice is interested in positive employee outcomes. Even though research has examined a host of work factors ranging from personality and emotions to leadership and culture, it is not clear how factors outside of work such as lifestyle influence employee performance and satisfaction. We develop theory on health conscious identity as it affect important work outcomes. We draw on emerging societal trends to outline how exercise affect employee job performance and life satisfaction. We also contend that health conscious identity has positive effect on employee job performance and life satisfaction. Our study integrates facets such as media influence, pandemic effect, and recommendations from health authorities with conventional issues of employee attitude, behavior, and well-being. Data from 280 employees and 58 supervisors supported the hypothesized relationships. We discuss implications on organizational practices in the emerging work order and suggest future research directions.
Keywords: organizational psychology; lifestyle; health conscious identity; exercise; performance; satisfaction